Validity and Reliability of Higher Order Thinking Test Instrument Development Skills: systematic literature reviews - Teguh Febri Sudarma; irfandi irfandi; Festiyed Festiyed; Yuni Adha; Yerimadesi Yerimadesi (Universitas Negeri Medan, 2023)
Higher Order Thinking Skill (HOTS) is the ability to think that does not simply recall, restate, or refer without reciting. HOTS questions in the context of assessment measure the ability to transfer one concept to another, process and apply information, find links from various information, use the information to solve problems, and critically examine ideas and information. In this study, 17 articles were used, which included 14 national articles and 3 international articles. The seventeen articles discussed the development of the Higher Order Thinking Skill Test Instrument Development instrument. The test instrument developed contains Higher Order Thinking Skills. Based on the results of the meta-analysis research, it can be concluded that the validity value of the seventeen journals is 1.85 with a high category. The reliability value is 0.615 to 0.94 with a high category. Development based on the level of study is still piled up at the junior and senior high school levels